Room temperature AlInAs/InGaAs/inP quantum cascade lasers - Gutowski, Piotr; Karbownik, Piotr; Trajnerowicz, Artur; Pierściński, Kamil; Pierscińska, Dorota; Sankowska, Iwona; Kubacka-Traczyk, Justyna; Sakowicz, Maciej; Bugajski, Maciej (Photonics Letters of Poland, 2014)
The room-temperature (300 K), pulsed mode operation of InP-based quantum cascade laser (QCL) is reported. This has been achieved by the use of lattice matched AlInAs/InGaAs/InP heterostructure. Its design follows a 4-well, 2-phonon resonance scheme. The QCL structures were grown by MBE in Riber Compact 21T reactor. The lasers utilize AlInAs waveguide and were grown exclusively by MBE without MOVPE regrowth. High operating temperatures have been achieved by careful optimization of growth and processing technology. Full Text: PDF References M. Beck, D. Hofstetter, T. Allen, J. Faist, U. Oesterle, M. Ilegems, E. Gini, H. Melchior, "Continuous Wave Operation of a Mid-Infrared Semiconductor Laser at Room Temperature", Science 295, 301 (2002) CrossRef FIMMWAVE ver. 5.3.9, Photon Design, www.photond.com K. Pierściński, D. Pierścińska, M. Iwińska, K. Kosiel, A. Szerling, P. Karbownik, and M. Bugajski, "Investigation of thermal properties of mid-infrared AlGaAs/GaAs quantum cascade lasers", J. Appl. Phys. 112, 043112 (2012) CrossRef M. Bugajski, K. Kosiel, A. Szerling, P. Karbownik, K. Pierściński, D. Pierścińska, G. Hałdaś and A. Kolek, "High performance GaAs/AlGaAs quantum cascade lasers: optimization of electrical and thermal properties", Semiconductor Lasers and Laser Dynamics V, K. Panajotov, M. Sciamanna, A. Valle, R. Michalzik, (eds.), Proc. of SPIE Vol. 8432, 84320I (2012) CrossRef J. Faist, "Quantum Cascade Lasers", Oxford University Press, Oxford 2013